Patterns of Histopathological Changes in Kidney in Phosphorus Poisoning- An Autopsy Finding (Journal of Forensic Medicine & Toxicology, 2025)
Background Yellow phosphorus is a toxic, nonmetallic inorganic substance used in various sectors, such as fireworks, firecrackers, rodenticides, ammunition, match industries and fertilizers. We report a case of phosphorus poisoning with histopathological changes in the kidney. Case description An 18 years old male died from the consumption of rat poison (contains yellow phosphorous). On postmortem examination, yellowish discoloration was seen all over the body. Internal examination showed edematous brain. Yellowish discoloration with hemorrhagic areas was seen in the cerebellum along with yellowish discoloration of both liver and kidney. On histopathological examination of kidney, the proximal tubular epithelial cells were predominantly affected by diffuse cytoplasmic vacuolation. Glomerular epithelial cells showed cloudy swelling. No significant interstitial inflammation/tubulitis was seen.
Keywords: Yellow phosphorous; poisoning; histopathology; proximal tubular epithelial cells; glomeruli.